Теоретичні аспекти трансформації інституту корупційних злочинів - Михайленко, Дмитро Григорович; Михайленко, Дмитрий Григорьевич; Mihajlenko, Dmitrij (Одеса : Юрид. л-ра, 2014)
The article focuses on certain problems of the Criminal Code of Ukraine under the conditions of enhancement of the legal mechanism of fight against corruption crimes. The imperfection of the Criminal Code is shown in regard to establishing the grounds of criminal liability of legal entities. The structure of a target of corruption crimes is described as a group of guarded legal relations. A hypothesis about the establishment of a model of criminal law fight against corruption based on the principle of “multiple bor- derlines” is set up. The urgency and necessity of constructing a new scientific theory of corruption crimes is substantiated.
Михайленко Д. Г. Теоретичні аспекти трансформації інституту корупційних злочинів / Д. Г. Михайленко // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 338-346.
Keywords: корупція; корупційні злочини; кримінальна відповідальність юридичних осіб; особи, які надають публічні послуги; теорія корупційних злочинів; коррупция; коррупционные преступления; уголовная ответственность юридических лиц; лица, которые предоставляют публичные услуги; теория коррупционных преступлений; corruption; corruption crimes; criminal liability of legal entities; public service providers; the theory of corruption crimes